Molecular identification of Scopellaria marginata from East Java, Indonesia, based on trnL-UAA and trnL-trnF intergenic spacer regions - TURHADI TURHADI; BRILIYAN NATALINA SUDARJAYANTI; FIFI MAR’ATUN SOLIHAH; RODIYATI AZRIANINGSIH; MUFIDAH AFIYANTI; ESTRI LARAS ARUMINGTYAS (Smujo International, 2024)
Abstract. Turhadi, Sudarjayanti BN, Solihah FM, Azrianingsih R, Afiyanti M, Arumingtyas EL. 2024. Molecular identification of Scopellaria marginata from East Java, Indonesia, based on trnL-UAA and trnL-trnF intergenic spacer regions. Nusantara Bioscience 16: 111-118. Scopellaria marginata (Blume) W.J.de Wilde & Duyfjes is a wild species in Cucurbitaceae, which was recorded as new expanding their distribution in East Java, Indonesia. The trnL-UAA and trnL-trnF intergenic spacer (IGS) sequences of Scopellaria are still limited in publicly accessible databases. This study aimed to evaluate the trnL-UAA and trnL-trnF IGS sequences of S. marginata from Malang, East Java. Total DNA of S. marginata was used to amplify the trnL-UAA and trnL-trnF IGS region. Then, the PCR products are sequenced using bi-directional Sanger dideoxy sequencing to obtain the DNA sequence of those two regions. The results showed that the partial sequences of S. marginata for trnL-UAA ranged from 528 to 571 bp, while the sequence for trnF-trnL IGS ranged from 434 to 445 bp. The S. marginata samples are similar to S. marginata in the database with similarity levels of 97.14-97.50% and 98.36-98.61%, respectively, based on the trnL-UAA and trnL-trnF IGS. Both trnL-UAA and trnL-trnF IGS showed a Correct Assignment Rate (CAR) of 100% for S. marginata. Two-dimensional DNA barcoding with lengths 505 and 417 bp for trnL-UAA and trnL-trnF IGS proposed as specific barcodes for S. marginata. These results prove that Malang, East Java was an additional distribution area for S. marginata in Indonesia.